Meningkatkan Kemampuan Problem Solving Matematika Siswa Sd Melalui Implementasi Model Problem Based Learning - mrizkidirmansyah; Riduan Febriandi (Elementary Teacher Education Program, Majalengka University, 2023)
This research aims to find out whether the problem based learning model can improve abilitiesproblem solving elementary school student mathematics. The research was carried out at SD Negeri 38 Lubuklinggau. This type of research is classroom action research. Data collection techniques are carried out using tests, observation and documentation. The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research consists of 2 cycles with research procedures using the Kemmis & McTaggart model which includes planning, implementing actions, observing and reflecting. The research results show that there has been an increase in abilityproblem solving fourth grade student at SD Negeri 38 Lubuklinggau. This can be seen from the increase in abilityproblem solving Students' mathematics from the pre-cycle condition was 49.8% and increased in cycle 1 with an average score of 65%. Then in cycle 2, a significant increase was obtained with the average ability value obtainedproblem solving student mathematics is 76.8. From the research results, it was concluded that the modelproblem based learning can improve abilitiesproblem solving mathematics for fourth grade students at SD Negeri 38 Lubuklinggau.